Pengaruh Ekoefisiensi dan Akuntansi Lingkungan Terhadap Kinerja Keuangan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019-2021) - Nova Eliza Tamaroh; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2023)
Financial performance is the result of the company's management insistence that is needed by the company to know and evaluate the level of success of the company based on the financial activities that have been carried out. The purpose of this study was to find out about the effect of eco-efficiency, accounting environment, size and capital structure on financial performance both simultaneously and partially. The research method uses a correlational method with a quantitative approach. The data used are secondary data with a research time series of three years. The population used is manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 period. The sampling technique used purposive sampling and obtained 159 companies that were sampled for three years. Data analysis using multiple linear regression analysis. While data processing uses IBM Statistical Package for the Social Sciences type 26. The results of this study explain that eco-efficiency and environmental accounting have a positive and significant effect on financial performance in manufacturing companies, size has a negative and significant effect on financial performance in manufacturing companies and the capital structure is not effect on financial performance in manufacturing companies.Keywords: Eco-efficiency, accounting environment, size, capital structure and financial performance